Jet-driven bubbles in Fanaroff–Riley type-I sources. Issue 4 (5th August 2019) - Irwin, Christopher M; Tang, Xiaping; Piran, Tsvi; Nakar, Ehud
Abstract: Observations of several Fanaroff–Riley (FR) type-I sources reveal outflowing bipolar bubbles of hot gas surrounded by a weak forward shock. We consider the possibility that these bubbles were driven by choked relativistic jets that failed to penetrate the ambient intracluster medium. Using new results on choked jets linking the geometry of the forward shock to the jet properties, we infer robust limits on the radius R ch at which the jet was quenched in five well-studied FR type-I sources, finding typically R ch ∼ 10 kpc. We further show that, in order to reach this radius in less than the current age of the system, the jet must have been tightly collimated, with the jet head subtending an angle of θ _h2^° . The ambient pressure is not high enough to explain this collimation, suggesting that the jet was collimated by interaction with its own cocoon. Although the choking radius is well-constrained, we find a degeneracy between the initial jet opening angle before collimation, θ0, and the duration of jet activity, t b, with (t_b/1Myr)(θ _0/5^° )^-20.1 . We speculate that the working time and/or opening angle of the jet may be important factors contributing to the FR type-I/type- II morphology in galaxy clusters, with short-lived or wide jets being choked to form bipolar bubbles filled with diffuse radio emission, and longer-lived or narrow jets successfully escaping the cluster core to produce cocoons with radio hotspots.